2020
DOI: 10.1002/pen.25558
|View full text |Cite
|
Sign up to set email alerts
|

Study on the interfacial interactions and adhesion behaviors of various polymer‐metal interfaces in nano molding

Abstract: This study focuses on investigating interfacial interactions and the adhesion mechanism of polymer‐metal interfaces in nano‐molding. Polyphenylene sulfide (PPS), polyamide 6 (PA6), and isotactic polypropylene (iPP) were chosen as candidate polymers, and aluminum (Al), and copper (Cu) were used as metal substrates. By establishing the metal matrix composed of a rectangular pit with length, width, and depth of 4.5, 4.5, and 2.0 nm, respectively, six paired polymer‐metal interfacial systems in a cuboid of 7.5 × 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The strength of the joining at the polymer-metal interface mainly depends on the non-bonding interaction, which can be characterized by the interfacial energy (nonbonding interaction energy). To directly judge the strength of the interaction between the polymer molecule and the aluminum substrate based on the numerical magnitude, the binding energy is defined as the negative value of the interaction energy between the polymer molecule and the metal substrate surface E interation ¼ ÀΔE ð Þ : In the nano-injection molding process, the van der Waals' non-bonding interaction energy and electrostatic interactions in the polymer-metal interface can be calculated by [18] ,…”
Section: Interface Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the joining at the polymer-metal interface mainly depends on the non-bonding interaction, which can be characterized by the interfacial energy (nonbonding interaction energy). To directly judge the strength of the interaction between the polymer molecule and the aluminum substrate based on the numerical magnitude, the binding energy is defined as the negative value of the interaction energy between the polymer molecule and the metal substrate surface E interation ¼ ÀΔE ð Þ : In the nano-injection molding process, the van der Waals' non-bonding interaction energy and electrostatic interactions in the polymer-metal interface can be calculated by [18] ,…”
Section: Interface Energymentioning
confidence: 99%
“…Mori and Matubayasi [16,17] reported that the molecular scale of the polymer and the size of the nano-cavity in the metal matrix impact the filling rate in nanoinjection molding. Liu et al [18] discovered that polymers of different polarities are related to the slippage of the nano-injection mold cavity wall. Additionally, the separation process of the polymer-metal interface should be noted.…”
Section: Introductionmentioning
confidence: 99%
“…The corona-treated PET film's surface group and the small surface energy difference between the PET films and developed ink may also help to anchor with each other. [23][24][25][26] 3.3.7 | Rub resistance study Rub resistance is a significant property of ink, which provides readability of text matter or any defect in printing design visibility. During the supply chain of packaging materials, they experience the rough and uneven conditions of the road.…”
Section: Adhesion Performance Of Inks On Pet Filmmentioning
confidence: 99%
“…Each nucleus is considered to move according to Newton's law under the action of the empirical potential field provided by other nucleus and electrons. Nowadays, the MD method has been widely used in injection molding to analyze the molding quality of molding parts, [ 18‐20 ] the demolding quality, [ 21 ] geometrical morphologies of parts, [ 22 ] and even filling behavior of array structures. [ 23 ] It is well known that the MD simulations are all in the nanoscale because the limited computational power and the experimental measurements are usually in the microscale for the requirements of test conditions and accuracy.…”
Section: Introductionmentioning
confidence: 99%